1986
DOI: 10.1055/s-2007-1012383
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prolactin Secretion in Canine Pituitary-Dependent Hyperadrenocorticism

Abstract: In 15 dogs with pituitary-dependent hyperadrenocorticism (PDH) the basal prolactin concentrations (means of 6 determinations; range 2.8-24.7 micrograms/l) were significantly higher than those of 23 healthy control dogs (0.9-10.5 micrograms/l). In five dogs with hyperadrenocorticism due to adrenocortical tumour (ATH) the prolactin concentrations were also significantly elevated, but still significantly lower than the values of the dogs with PDH. The prolactin concentrations of the dogs with PDH responded supran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The limit of detection for LH was 0•31 µg/l and the intraand interassay coefficients of variation were 2•3% and 10•5%, respectively. Plasma PRL was measured in a heterologous RIA (Stolp et al 1986). The limit of detection was 0•8 µg/l plasma.…”
Section: Hormone Determinationmentioning
confidence: 99%
“…The limit of detection for LH was 0•31 µg/l and the intraand interassay coefficients of variation were 2•3% and 10•5%, respectively. Plasma PRL was measured in a heterologous RIA (Stolp et al 1986). The limit of detection was 0•8 µg/l plasma.…”
Section: Hormone Determinationmentioning
confidence: 99%
“…Prolactin concentrations were determined by a previously validated heterologous radioimmunoassay (22). LH concentrations were determined by a heterologous radioimmunoassay as described Calculations and statistical analysis of the data The progesterone release after day 33 was compared with the total progesterone release of the luteal period and defined by measurement with a digital planimeter (Haff; West Germany) of the surface areas limited by the lines of the progesterone level and the Xaxis from day 1 and 33 to the end of the luteal period.…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…In their study, pituitary responses were evaluated by a combination stimulus of hypothalamic hormones, which showed that the PDH dogs had augmented PRL response clearly higher than normal dogs. Another in vivo study using the dogs with hyperadrenocorticism due to adrenocortical tumors (ATH) also exhibited increased levels of serum PRL [16], although the PRL secretion in the ATH dogs normally responded to exogenous bromocriptine or TRH [16]. Given that amelioration of hypercortisolemia by adrenalectomy has normalized serum PRL levels in our Cushing's case, hypercortisolemia is most likely to be involved in the coexisting hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 75%